Undiagnosed Diabetes Mellitus and Its Predictors Among Socially Marginalized Menja Communities in Southwest Ethiopia - Ashenafi Assefa; Nigusie Shifera (Frontiers in Public Health, 2022)
Background:Diabetes mellitus (DM) is a metabolic disorder marked by a persistently high blood glucose level over a prolonged period of time linked to either defects in insulin secretion, insulin action, or both. It is responsible for 537 million adult cases and 6.7 million deaths in 2021. However, about half of the people with diabetes go undiagnosed. Low-income and socially disadvantaged communities are the most vulnerable to the disease. Despite this fact, nothing has been done among these communities, so this study aimed to assess the extent of undiagnosed diabetes and its predictors among the socially marginalized Menja communities of Southwest Ethiopia, 2021.MethodsA community-based cross-sectional study was done in the Menja communities from April 21/2021 to June 30/2021. The required sample size was calculated using the single population proportion formula and systematic sampling techniques were employed to select the households. Data were collected through face-to-face interviews utilizing an interviewer-administered questionnaire to collect socio-demographic and behavioral characteristics, and anthropometric measurements were taken from each participant. Diabetes was defined as participants who had an FBG ≥ 126 mg/dL or RBG > 200 mg/dL. The multivariate logistic regression model was used to identify the predictors of diabetes; adjusted OR with a 95% CI was computed to assess the strength of associations.ResultsThe prevalence of undiagnosed DM among the socially marginalized Menja communities was 14.7% [95% CI: (11.1–18.3)], and sex-specific prevalence was 16.8%, and 11.1% for men and women respectively. Factors like alcohol consumption (AOR = 3.0, 95% CI 1.49 to 6.05), family history of DM 4.4 (AOR = 4.37, 95% CI 2.04 to 9.35), lower vegetable consumption 3.5 (1.19–10.31) (AOR = 3.5, 95% CI 1.19 to 10.31), and less physical exercise 3.3 (AOR = 3.34, 95% CI 1.61 to 6.90) were the independent predictors that increase the risk of diabetes among Menja communities.Conclusion and RecommendationsUndiagnosed diabetes was high as compared to other settings. Alcohol use, family history of diabetes, vegetable consumption, and physical exercise were predictors of diabetes. Hence, the study suggests frequent screening and treatment for high-risk groups. Minimizing alcohol drinking, frequent vegetable consumption, and physical exercises were recommended measures for the prevention and control of DM among the population of Ethiopia.